The Interface Between Sustainability and Technology in Tourism: A Transformative Learning Perspective - Arici, Hasan Evrim; Saydam, Mehmet Bahri (Springer Nature, 2022)
This chapter seeks to discuss and provide a conceptual framework that explains the interface of sustainability and technology from the standpoint of transformative learning theory. Broadly speaking, the current chapter highlights the indispensable role of technology in sustainable development. Although many academic studies in extant literature have touched upon the link between sustainability and technology, to our best knowledge, only a few studies have shown the necessary effort and importance in integrating technology into sustainable development elements. The chapter takes a conceptual approach to this gap in the literature and explains the importance of technology in sustainable development, offering significant theoretical and practical implications. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.